A critical evaluation of quantitative and qualitative analysis by means of energy-dispersive X-ray measurement in a scanning electron microscope - Blum, F (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1978.